PENERAPAN ALGORITMA C4.5 DALAM MENGENALI POLA PERKEMBANGAN PEKERJAAN PROYEK - Laila, Rahmah; Hendra, Syaiful; Azhar, Ryfial; Anwar, Asriani; Ngemba, Hajra Rasmita (Fakultas Teknik, Universitas Tadulako, 2020)
PLN UPP KITRING Central Sulawesi has duties and responsibilities in the process of supervising the construction period until the completion of the contract mass. In this monitoring process, managers find it very difficult to know the progress of the project due to the absence of media to facilitate reporting and monitoring of system developments to find out follow-up to the system. If this problem is allowed to continue, the project work cannot be completed on time and incurs a considerable cost loss. Through this research, it is hoped that it can help solve project monitoring problems by identifying patterns of project development that will be useful for managers in making decisions related to project performance. The development of this research uses the waterfall method and the system testing uses a black-box testing. The results of this study are based on testing and design analysis of the C4.5 Algorithm Application in Recognizing Project Work Development Patterns to Know the Win/Lose Target Results of the Case Study Project at PT PLN (PERSERO) UPP KITRING Central Sulawesi, it can be concluded that the system is able to recognize patterns project development by utilizing the C4.5 algorithm and the system can implement the C4.5 algorithm in recognizing project development patterns.